Conus medullary syndrome secondary to spinal schwannoma: a good surgical outcome of 3 cases - Mor Japar Khan, Ed Simor Khan; Ismail Mansor, Nur Akmal; Sharifudin, Mohd Ariff; Ayeop, Mohd Adham Shah; Zakaria@Mohamad, Zamzuri; Chan, Kin Hup; Awang, Mohamed Saufi (2014)
Spinal Schwannoma originates form the sheath of spinal cord roots - neurilemma or Schwann cells, so it is mainly called neurilemmoma or Schwannoma. Spinal schwannomas account for about 25% of primary intradural spinal cord tumors in adults population but less common in children. The tumor localization is in various parts of spinal cord, but prevails in cervical and thoracic, rare in lumbar and sacral regions. In the literature 70 to 80% of spinal schwannomas are reported to be intradural in location, and 15% with both intradural and extradural components.